The age of chocolate: a diversification history of Theobroma and Malvaceae - Richardson, James E.; Whitlock, Barbara A.; Meerow, Alan W.; Madriñán, Santiago (Frontiers in Ecology and Evolution, 2015)
Dated molecular phylogenies of broadly distributed lineages can help to compare patterns of diversification in different parts of the world. An explanation for greater Neotropical diversity compared to other parts of the tropics is that it was an accident of the Andean orogeny. Using dated phylogenies, of chloroplast ndhF and nuclear DNA WRKY sequence datasets, generated using BEAST we demonstrate that the diversification of the genera Theobroma and Herrania occurred from 12.7 (11.6-14.9 [95% HPD]) million years ago (Ma) and thus coincided with Andean uplift from the mid-Miocene and that this lineage had a faster diversification rate than other major clades in Malvaceae. We also demonstrate that Theobroma cacao, the source of chocolate, diverged from its most recent common ancestor 9.9 (7.7-12.9 95% HPD) Ma, in the mid-to late-Miocene, suggesting that this economically important species has had ample time to generate significant within-species genetic diversity that is useful information for a developing chocolate industry. In addition, we address questions related to the latitudinal gradient in species diversity within Malvaceae. A faster diversification rate is an explanation for the greater species diversity at lower latitudes. Alternatively, tropical conditions may have existed for longer and occupied greater areas than temperate ones meaning that tropical lineages have had more time and space in which to diversify. Our dated molecular phylogeny of Malvaceae demonstrated that at least one temperate lineage within the family diverged from tropical ancestors then diversified at a rate comparable with many tropical lineages in the family. These results are consistent with the hypothesis that Malvaceae are more species rich in the tropics because tropical lineages within the family have existed for longer and occupied more space than temperate ones, and not because of differences in diversification rate.